1977
DOI: 10.1016/s0006-3495(77)85591-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 and proton magnetic resonance of mouse muscle

Abstract: It is shown that roughly 4 mmol carbon atoms/g mouse muscle can give rise to a "high resolution" 13C NMR spectrum. From the 13C spectrum, it is estimated that the protons from mobile organic molecules or molecular segments amount to 6-8%of total nonrigid protons (organic plus water) in muscle. Their spin-spin relaxation times (T2) are of the order of 0.4-2 ms. At 37 degrees C, the proton spin-echo decay of mouse muscle changes rapidly with time after death, while that of mouse brain does not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Also, the magnitude (11-15% MT, r) and T 2 value (Ͼ100 ms) of component D closely resemble those of the component attributed to extracellular fluid (4,15,20). Critics of the water compartment model have suggested that the ex vivo T 2 component attributed to extracellular fluid was a postmortum artifact (17), but the present observation of a similar component in vivo contradicts that argument. The relative volumes of the both the extra (M D )-and intracellular fluid (M B ϩ M C ) in resting muscle were in close agreement with values determined with radio tracers (8,26,36,40).…”
Section: Discussionsupporting
confidence: 62%
“…Also, the magnitude (11-15% MT, r) and T 2 value (Ͼ100 ms) of component D closely resemble those of the component attributed to extracellular fluid (4,15,20). Critics of the water compartment model have suggested that the ex vivo T 2 component attributed to extracellular fluid was a postmortum artifact (17), but the present observation of a similar component in vivo contradicts that argument. The relative volumes of the both the extra (M D )-and intracellular fluid (M B ϩ M C ) in resting muscle were in close agreement with values determined with radio tracers (8,26,36,40).…”
Section: Discussionsupporting
confidence: 62%
“…Foster et al (7) suggested that its source was relatively mobile protons in tissue protein and lipid. We compared the 13C and 'H spectra of skeletal muscje (8), and supported their suggestions. Recently, Peemoeller and Pintar (9) and Peemoeller et al (10) proposed that the fraction with a decay constant of -5 ms is due to protons in large molecules (,30%) plus protons in water (-70%).…”
Section: Discussionsupporting
confidence: 62%
“…The smaller slowly exchanging bound water fraction may determine much of the MR relaxation character of muscle cells. Muscle cell contraction involves conformational changes in the large contractile proteins as well as mechanical alterations in intracellular surfaces (11). Such surface alterations may affect the bound water layer, which in turn may determine MR relaxation (10).…”
Section: Rmmentioning
confidence: 99%